Hi everyone,

I don't remember how to complete the square with a -x^2. Could you please explain to me how to complete the square of 6+4x-4x^2?

Thank you

Printable View

- September 16th 2007, 04:20 PMchocolatelovercomplete the square
Hi everyone,

I don't remember how to complete the square with a -x^2. Could you please explain to me how to complete the square of 6+4x-4x^2?

Thank you - September 16th 2007, 04:33 PMKrizalid
- September 16th 2007, 04:48 PMticbol
Here is one way.

Remember, you "complete the square" only when the coefficient of the squared variable is 1.

6 +4x -4x^2

= -4x^2 +4x +6

= -4(x^2 -x) +6

Now, complete the square,

= -4(x^2 -x +(-1/2)^2 -(-1/2)^2) +6

= -4[(x -1/2)^2 -1/4] +6

= -4(x -1/2)^2 +1 +6

= -4(x -1/2)^2 +7

= 7 -4(x -1/2)^2 ----------answer.